Kolusi Algoritmik: Risiko Kolusi Terselubung AI Pricing dalam Persaingan Usaha - Sundari, Ariefah; Indriani, Arya Dhita; Nadzifah, Umi Nur (Jurnal Persaingan Usaha, 2025)
The rapid development of Artificial Intelligence (AI) in pricing strategies presents both opportunities and significant challenges for market competition. Algorithms designed to optimize pricing may unintentionally facilitate a new form of covert collusion, which is difficult for regulators to detect since it occurs automatically without explicit agreements between firms. This paper aims to analyze the phenomenon of algorithmic collusion in the context of competition law, with particular emphasis on its risks to the principles of fair competition. The study employs a normative-juridical approach through literature review, legal analysis, competition policy assessment, and international case studies. The findings indicate that pricing AI can generate market coordination resembling digital cartels, thereby challenging the effectiveness of existing legal instruments. The main conclusion highlights the urgent need for regulatory adaptation and technology-based oversight to enable competition authorities to anticipate and address algorithmic collusion. The implications of this study underscore the importance of collaboration among regulators, technology developers, and business actors in establishing a responsive legal framework to ensure fairness and sustainability in market competition.